Prevalence of Burnout Syndrome and Its Three Dimensions in Dental Faculty Members of Azad Dental University in 2008 - Nasrin Roghanizad; Mehdi Vatanpoor; S.Nazila Seddigh Oraee; Vandad Sharifi; Mehdi Abbasi (Islamic Dental Association of Iran, 2013)
Background and Aim: There is some evidence suggesting that dentists suffer a high level of occupational stress that can lead to burnout syndrome. The aim of this study was to evaluate the prevalence of burnout syndrome and its three dimensions in dental faculty members of Azad Dental University in 2008 .   Materials and Methods: In this descriptive cross - sectional study, 99 dental faculty members of Azad Dental University in Tehran were evaluated using a questionnaire consisting of 10 questions regarding demographic characteristics and 22 questions adapted from Maslach Burnout Inventory (MBI). Burnout was assessed with MBI in three dimensions of emotional exhaustion, depersonalization and personal accomplishment . The final scores were categorized as high, moderate and low based on standard test scores . Data were analyzed using linear regression test with Enter method .   Results: The prevalence of reduced personal accomplishment , depersonalization and emotional exhaustion was 19.1%, 7% and 4% among subjects, respectively. Work experience and weekly work hours did not have a significant association with occupational burnout (P>0.05) .   Conclusion: The mean overall score gained by dental faculty members of Tehran Azad Dental University showed a low prevalence of occupational burnout in comparison to national statistics .